Enhancing iPSC‐CM Maturation Using a Matrigel‐Coated Micropatterned PDMS Substrate. Issue 11 (16th November 2022) - Jimenez‐Vazquez, Eric N.; Jain, Abhilasha; Jones, David K.
Abstract: Cardiac myocytes isolated from adult heart tissue have a rod‐like shape with highly organized intracellular structures. Cardiomyocytes derived from human pluripotent stem cells (iPSC‐CMs), on the other hand, exhibit disorganized structure and contractile mechanics, reflecting their pronounced immaturity. These characteristics hamper research using iPSC‐CMs. The protocol described here enhances iPSC‐CM maturity and function by controlling the cellular shape and environment of the cultured cells. Microstructured silicone membranes function as a cell culture substrate that promotes cellular alignment. iPSC‐CMs cultured on micropatterned membranes display an in‐vivo‐like rod‐shaped morphology. This physiological cellular morphology along with the soft biocompatible silicone substrate, which has similar stiffness to the native cardiac matrix, promotes maturation of contractile function, calcium handling, and electrophysiology. Incorporating this technique for enhanced iPSC‐CM maturation will help bridge the gap between animal models and clinical care, and ultimately improve personalized medicine for cardiovascular diseases. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Cardiomyocyte differentiation of iPSCs Basic Protocol 2 : Purification of differentiated iPSC‐CMs using MACS negative selection Basic Protocol 3 : Micropatterning on PDMS